x + 2x = 10

common terms can be added together, in this case both the terms on left hand side have "x" as the common parameter.

Taking x as common parameter,

x (1+2) = 3x =10

or, **x = 10/3**

We can check the answer by substituting x =10/3 on left hand side of equation:

10/3 + 2 x 10/3 = 10/3 + 20/3 = (10+20)/3 = 30/3 = 10

which is same as right hand side, hence proved.

Ans: **x = 10/3**

Before solving this equation, we can simplify it. How?

In the equation:

**x + 2x **= 10

The bolded terms, **x** & **2x**, are **like terms, **which means that you can use operators to simplify them into one term. In this case, **x **can be added to **2x **to simplify the equation:

(**x + 2x**) = 10 -> **3x **= 10

Now, we have a simple equation. We know that 10 is the value for **3x,** so to find the value of **x, **we can use **inverse operations.** We know that if we apply something to one side of the equation, we must apply it to the other side too:

3x **/ 3 **= 10 **/ 3**

Therefore:

**x = 10/3** (The fraction is the most accurate way to describe the answer, since the actual answer has infinite decimals.)